Tainted Money? Contribution Limits and the Effectiveness of Campaign Spending - Thomas Stratmann (Center for Economic Studies and ifo Institute (CESifo), 2003)
Campaign expenditures are not effective in increasing candidates' vote shares if voters do not respond to the advertisement when they believe that campaign expenditures are financed with tainted money. In this situation, limiting contributions may reduce the number of policy favors that candidates promise to contributors, and thereby increase the effectiveness of campaign spending. Exploiting cross-state variation in campaign finance laws, this paper tests whether campaign expenditures by state House candidates are more productive in increasing vote shares when candidates run in states that limit contributions. The results show that campaign expenditures by incumbents, challengers, and open seat candidates are more productive when candidates run in states with campaign contribution limits, as opposed to in states without limits. Controlling for the endogeneity of incumbent spending, the study shows that in states with contribution limits, incumbent spending and challenger spending are equally productive, and that spending by both candidates is quantitatively important in increasing their vote shares.
Keywords: 330